2011
DOI: 10.1007/s00127-011-0365-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronic medical conditions mediate the association between depression and cardiovascular disease mortality

Abstract: Several levels of evidence suggest that the association between depression and CVD mortality is partially mediated by prevalent/incident chronic medical conditions, as well as unhealthy lifestyle behaviors. Patients presenting with clinically significant depressive symptoms, particularly if persistent, should be assessed for both chronic conditions and lifestyle risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 50 publications
1
25
0
1
Order By: Relevance
“…Chronic disease was related to depression in our study, which is similar to what has been reported in the literature (8,(16)(17)(18). Insufficient daily activities were related to depression too, and those who were satisfied with daily activities had less depression (19).…”
Section: Discussionsupporting
confidence: 90%
“…Chronic disease was related to depression in our study, which is similar to what has been reported in the literature (8,(16)(17)(18). Insufficient daily activities were related to depression too, and those who were satisfied with daily activities had less depression (19).…”
Section: Discussionsupporting
confidence: 90%
“…In the overall US adult population, the estimated prevalence of hyperlipidemia based on clinical data is 13.4% (NHANES, 2009-2010). 72 Estimates of the prevalence of hypertension (median: 35.0%; range: 10.0%-68.0%) among persons with SMI were extracted from 29 studies 43,46,47,50,53,56,57,60-68,70,71,73-83 (37 measures). The median prevalence estimates of hypertension among studies using claims (35.3%), clinical (37.8%) and other (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…3 A wide variety of demographic and lifestyle factors have been associated with depression. [2][3][4][5] Obesity, anxiety, insomnia, cardiovascular disease, diabetes, and lower urinary tract symptoms are conditions associated with an increased risk of depression and these have also been linked to sleep disorders 2,5,6 ; the most common sleep disorder in men is obstructive sleep apnea (OSA).…”
Section: Introductionmentioning
confidence: 99%